I'm a frog! - Willems, Mo (New York : Hyperion Books for Children, an imprint of Disney Book Group, 2013)
Piggie introduces his reluctant friend, Gerald the elephant, to the wonderful world of pretend.
Keywords: Imagination -- Fiction; Friendship -- Fiction; Pigs -- Fiction; Elephants -- Fiction; Humorous stories